Acquiescentia and Power in Spinoza’s Ethics - Noa Naaman-Zauderer (Journal of Modern Philosophy)
The challenge at the center of this paper is to reconcile three explicit assertions that Spinoza makes in his Ethics: 1. Rational self-esteem is “a joy born of the fact that a man considers himself and his own power of acting”; 2. The power of acting of each singular thing is nothing but the actual essence of the thing; 3. Reason cannot explain the essence of any singular thing. My aim in this paper is to provide an account of how reason, despite its inability to grasp singular essences, can make our singular power of acting accessible to us and thereby ground our proper self-esteem. I will argue that to resolve the puzzle, we must recognize a distinction, within the actual (durational) existence of any singular thing, between two senses of the term “power of acting,” or “perfection,” in accordance with the distinction between essence and existence of finite modes. On this basis, I will explain in what sense reason can be said to grasp our singular “power of acting” and to thereby ground our proper self-esteem, and how the twofold sense of “power of acting” underlies the distinction between rational self-esteem and the animi acquiescentia of intuitive knowledge.